Sofosbuvir‐based treatment regimens: real life results of 14 409 chronic HCV genotype 4 patients in Egypt. Issue 5 (9th January 2017) - Elsharkawy, A.; Fouad, R.; El Akel, W.; El Raziky, M.; Hassany, M.; Shiha, G.; Said, M.; Motawea, I.; El Demerdash, T.; Seif, S.; Gaballah, A.; El Shazly, Y.; et al.
Summary: Background: Chronic hepatitis C virus infection is one of the most important health problems in Egypt. The Ministry of Health's National Treatment Programme introduced sofosbuvir‐based therapy in October 2014. Aim: To assess the clinical effectiveness and predictors of response to SOF‐based treatment regimens, either dual therapy, with SOF/ribavirin (RBV) for 6 months or triple therapy with SOF/peg‐IFN‐alfa‐2a/RBV for 3 months, in a cohort of patients treated in National Treatment Programme affiliated centres in Egypt. Methods: Between October 2014 and end of 2014, patients who were eligible for treatment were classified according to their eligibility for interferon therapy: Group 1 (interferon eligible) were treated with triple therapy for 12 weeks and Group 2 (interferon ineligible) were treated with dual therapy for 24 weeks. Difficult to treat patients included those with F3‐F4 on Metavir score, Fib‐4 >3.25, albumin ≤3.5, total Bilirubin >1.2 mg/dL, INR >1.2 and platelet count <150 000 mm 3 . Results: Twelve weeks post‐treatment data were available on 14 409 patients; 8742 in group 1 and 5667 in group 2. In group 1, the sustained virological response at week 12 (SVR12) was 94% and in group 2 the SVR12 was 78.7%. Multivariate logistic regression analysis in which treatment failure is the dependent variable was done. Male gender, being a difficult to treat patient and previous interferon therapy were significant predictors of nonresponse in both treatment groups. Conclusion: Results of sofosbuvir‐based therapies in Egypt achieved similar rates of SVR12 as seen in phase III efficacy studies.